Landscapes of possibility. When autobiography becomes autoethnography - Bohme, Helen (Murmurations: Journal of Transformative Systemic Practice, 2022)
With many years of experience as a family therapist I became a researcher and embarked upon a Professional Doctorate in Systemic Practice. I had wanted to illuminate the art, craft, and the aesthetics therapy where therapist expertise is creating the space for and architecting a dialogical process. Traditional research methods were too limiting for this project so I created my own bespoke methodology. This paper shows examples of how I have blended reflection on personal and professional experiences and conversational storytelling in writing my doctoral thesis. I discuss details of my methodological journey and articulate these ideas through the creative use of two reflexive dialogues. These illuminate the value of systemic conversation and storytelling, how we make meaning and sculpt our identities.